2003
DOI: 10.1209/epl/i2003-00403-3
|View full text |Cite
|
Sign up to set email alerts
|

New magnetic structure study of TbNi 5 : Evidence of incommensurate structure

Abstract: RENi 5 (RE=rare-earth ions) intermetallic compounds crystallize in the hexagonal CaCu 5 structure (space group P6/mmm) [1] and have been extensively studied for various reasons over the last decades. Magneto-crystalline anisotropy of rare-earth ions as well as indirect exchange interaction between them, so-called RKKY interaction, is important to understanding the magnetism of these systems.We have investigated the magnetic structure of TbNi 5 using neutron diffraction from 2.2 to 30 K using neutron diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…This indicates the onset of long range ferromagnetic ordering in the system. No superlattice reflections were observed, which rules out any antiferromagnetic ordering, unlike in the case of TbNi 5 [8]. The ferromagnetic nature below 100 K is in conformity with the magnetization measurements, which shows an increase in the magnetization with lowering the temperature below 100 K. The best solution for the magnetic structure was arrived by placing the magnetic moment on Tb ion only.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…This indicates the onset of long range ferromagnetic ordering in the system. No superlattice reflections were observed, which rules out any antiferromagnetic ordering, unlike in the case of TbNi 5 [8]. The ferromagnetic nature below 100 K is in conformity with the magnetization measurements, which shows an increase in the magnetization with lowering the temperature below 100 K. The best solution for the magnetic structure was arrived by placing the magnetic moment on Tb ion only.…”
Section: Resultssupporting
confidence: 72%
“…Among these compounds, TbNi 5 has received the attention of many researchers. There are a few reports on the magnetic and neutron diffraction studies in TbNi 5 and its derivatives [7][8][9][10][11][12]. The ordering temperature (T C ) of TbNi 5 is 24 K. However, below this temperature, it is not a collinear ferromagnet, but is reported to possess a modulated ferromagnetic structure [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using unpolarized neutron diffraction on poly-and single crystalline TbNi 5 samples we first found magnetic satellites besides the previously reported ferromagnetic contributions to Bragg reflections [16,17]. We then described the magnetic ordering in TbNi 5 as a fan-like incommensurate structure with the wave vector k ¼ 2p=cð0; 0,0:019Þ for temperatures between T P ¼ 23 K and T L ¼ 10 K. Below T L the TbNi 5 undergoes another magnetic phase transition from the incommensurate phase to a so-called ''lock-in'' phase.…”
Section: Introductionmentioning
confidence: 58%
“…Our previous neutron diffraction studies of poly crystalline and single crystal TbNi 5 [15,16] showed that the Bragg reflections and magnetic satellites exist in all neutron diffraction patterns (NDPs) obtained at temperatures below T p . The NDPs can be described well on the assumption that in TbNi 5 there is formed a fanlike magnetic structure with two wave vectors k 1 = 0 and k 2 = 2πc/(0, 0, τ) with τ ≈ 0.18.…”
Section: Introductionmentioning
confidence: 99%